Bibliometric and visualized analysis of 3D printing bioink in bone tissue engineering - Xu, Kaihao; Yu, Sanyang; Wang, Zhenhua; Zhang, Zhichang; Zhang, Zhongti (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Background: Applying 3D printed bioink to bone tissue engineering is an emerging technology for restoring bone tissue defects. This study aims to evaluate the application of 3D printing bioink in bone tissue engineering from 2010 to 2022 through bibliometric analysis, and to predict the hotspots and developing trends in this field. Methods: We retrieved publications from Web of Science from 2010-2022 on 8 January 2023. We examined the retrieved data using the bibliometrix package in R software, and VOSviewer and CiteSpace were used for visualizing the trends and hotspots of research on 3D printing bioink in bone tissue engineering. Results: We identified 682 articles and review articles in this field from 2010 to 2022. The journal Biomaterials ranked first in the number of articles published in this field. In 2016, an article published by Hölzl, K in the Biofabrication journal ranked first in number of citations. China ranked first in number of articles published and in single country publications (SCP), while America surpassed China to rank first in multiple country publications (MCP). In addition, a collaboration network analysis showed tight collaborations among China, America, South Korea, Netherlands, and other countries, with the top 10 major research affiliations mostly from these countries. The top 10 high-frequency words in this field are consistent with the field’s research hotspots. The evolution trend of the discipline indicates that most citations come from Physics/Materials/Chemistry journals. Factorial analysis plays an intuitive role in determining research hotspots in this sphere. Keyword burst detection shows that chitosan and endothelial cells are emerging research hotspots in this field. Conclusion: This bibliometric study maps out a fundamental knowledge structure including countries, affiliations, authors, journals and keywords in this field of research from 2010 to 2022. This study fills a gap in the field of bibliometrics and provides a comprehensive perspective with broad prospects for this burgeoning research area.